Muchisse TM Coffeehouse a business proposal for small scale coffee shop enterprise - Ferrer, Danica M. (2010)
Some people say drinking coffee in the morning would start your day right. Around the world, people drink coffee usually at home, during mornings before attending to work since coffee is an effective stimulant. Apparently, because of the changing trend, consumption of coffee became a necessity rather than a luxury. Coffee is a universal in its appeal. People love to drink coffee because of its two-fold effect ? the pleasurable sensation and the increased efficiency it produces. With this, the need to have a coffee other than having it at home come into view; here came forth coffee shops. MuchisseTM Coffeehouse is a partnership, small-scale business enterprise that offers the urban-rural community of Mintal coffees, teas and snacks that will provide them the relaxing feel they crave for and would also stimulate their body in a strenuous, workload day. The shop will be located in Mintal, Davao City. This is the first of its kind coffee shop in Mintal offering products that were close to that found in most coffee shops situated in the downtown area except that it is offered in reasonable and affordable prices that fit the Mintal people?s buying capacity. With this, those who are in Mintal and crave for a quite place to work, socialize, and relax with coffee without needing to go downtown. MuchisseTMCoffeehouse is the right place for you. The company?s target market are professionals and college student residing, studying and working in Mintal. A market research was conducted in Mintal to assess the feasibility and profitability of the business if ever it will be established in the area. It was evident in the result that most of our respondents want to have coffee shop in Mintal. Through this, we assume that the business may prosper in the area. We envision being the number to be one café choice of students and professionals in the Mintal area.
Thesis (BS Food Technology) -- University of the Philippines Mindanao, 2010
Keywords: Coffeehouse; Coffee